1987
DOI: 10.1016/0014-5793(87)80849-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prostaglandins on the lipid transfer between human high density and low density lipoproteins

Abstract: Prostaglandin (PG) El was demonstrated to stimulate the transfer of phosphatidylcholine and cholesterol esters from human high density lipoproteins (HDL3) to low density lipoproteins (LDL). The enhancement effect of PGE~ on the interlipoprotein lipid transfer was seen at low PG concentrations under conditions of spontaneous exchange as well as in the presence of lipoprotein-depleted plasma, or partly purified plasma lipid exchange protein. PGE2 and PGF2~ showed no significant influence on the interlipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In principle, such influence of PGE 1 on the esterification of cholesterol could be attributed to interaction of the prostaglandin either directly with LCAT or with high density lipoprotein (HDL) apolipoprotein A1 (apo-A1) which is known to be a cofactor of the LCAT reaction. However, when lipoprotein-depleted plasma was incubated with phosphatidylcholine-cholesterol liposomes or with HDL recombinants obtained from purified apo-A1, egg lecithin and cholesterol, no enhancing effect of PGE1 was seen (7). Neither could we observe any stimulation of the LCAT reaction by PGE1 when the prostaglandin was incubated with lipid-depleted plasma and either HDL or low density lipoprotein (LDL).…”
Section: Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…In principle, such influence of PGE 1 on the esterification of cholesterol could be attributed to interaction of the prostaglandin either directly with LCAT or with high density lipoprotein (HDL) apolipoprotein A1 (apo-A1) which is known to be a cofactor of the LCAT reaction. However, when lipoprotein-depleted plasma was incubated with phosphatidylcholine-cholesterol liposomes or with HDL recombinants obtained from purified apo-A1, egg lecithin and cholesterol, no enhancing effect of PGE1 was seen (7). Neither could we observe any stimulation of the LCAT reaction by PGE1 when the prostaglandin was incubated with lipid-depleted plasma and either HDL or low density lipoprotein (LDL).…”
Section: Reviewmentioning
confidence: 80%
“…Neither could we observe any stimulation of the LCAT reaction by PGE1 when the prostaglandin was incubated with lipid-depleted plasma and either HDL or low density lipoprotein (LDL). Only when both HDL and LDL were present in the incubation mixture, was PGE1 able to stimulate the esterif'cation of LDLcholesterol (7). We presumed, therefore, that the effect of PGE1 on cholesterol esterification in plasma could be caused by prostaglandin-induced enhancement of interlipoprotein transfer of the substrates and (or) products of LCAT.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that prostaglandin E1 (PGE~) enhances the transfer of phosphatidylcholine and cholesterol esters from high-density lipoproteins (HDLs) to low-density lipoproteins (LDLs) [1]. This effect of PGE1 on the lipoprotein-lipid transfer was observed under conditions of spontaneous exchange as well as in the presence of lipoprotein-depleted plasma.…”
Section: Introductionmentioning
confidence: 93%
“…This effect of PGE1 on the lipoprotein-lipid transfer was observed under conditions of spontaneous exchange as well as in the presence of lipoprotein-depleted plasma. An enhanced lecithin acetyl-cholesteryl transferasecatalysed cholesterol esterification in plasma was demonstrated as a result [1]. One key determinant might be a direct PGEl-lipoprotein interaction via short-lived complexes [2].…”
Section: Introductionmentioning
confidence: 99%